The characteristic polynomial and the Cayley-Hamilton theorem. The trace and the determinant maps (Eurasian Journal of Physics,Chemistry and Mathematics, 2026)
In this paper, we provid a information the characteristic polynomial and the CayleyHamelton theorem, the trace and the determinant maps discuss the application of the theorem, and demonstrate its implementation in the OMOUS- 2024 and BIMO- 2026 olympiads.